The Routes of Migration: A Multifaceted Evidences from India - Praveen Naik Bellampalli; Yadava Neelam (Asian Social Work Journal, 2021)
This article examines the trend and patterns of migration in India. Internal and international migration occurs in search of survival, fulfilment, and a better life. Over the last few decades, major driving forces for urbanisation all over the world and is of concern in Asia due to the raising magnitude. Hence, Due to urbanization and globalization generate enormous opportunities for employment and livelihood for people in the country. The large numbers of people moving internal migration as well as international migration in the different part of the countryside. Thus, the article discussed some of the important theoretical underpinnings of the issue of migration as reflected from India. However, this paper would orient towards the protection of labour rights and promote safe and secure working environments of the migrant workers, which will be a key to achieving the agenda of Sustainable Development Goal (SDGs) 2030.